The Role of Well-Being, Supervisor Support and Positive Feedback on Lecturers’ Work Engagement - Hamzah, Hazalizah; Nordin, Nabilah Syuhada; Dwiyanti, Retno; Na’imah, Tri; Mawi, Nadzirah (The Journal of Behavioral Science, 2021)
This study aimed to evaluate job-related affective well-being, perceived supervisor support and positive feedback as contributing factors to work engagement of lecturers in the context two countries in the South East Asia. A total of 134 lecturers of one university in Malaysia and one university in Indonesia were recruited through simple random sampling. The research instruments were Job Affective Well-Being Scale, Survey of Perceived Supervisor Support and Utrecht Work Engagement Scale, while the statement of positive feedback was given in a hardcopy form or via personal e-mail. Multiple regression analysis showed that job affective well-being (β = 0.49, p = .01) and perceived supervisor support (β = 0.27, p = .01) made significant contribution to the prediction of work engagement. However, positive feedback statement (β = 0.02, p = .75) was not a significant predictor of work engagement. Therefore, a better strategy of the implementation of positive feedback should be considered in future so that the factor of why positive feedback may not have contributed to work engagement of lecturers can be indicated. Moreover, future studies should incorporate the elements of trust and respect in supervisory support to explore their roles in maintaining employee’s work engagement at workplace. The main implication of this research is it that the management of tertiary education should practice measures to increase perceived supervisor’s support among lecturers so that there will be more engagement at workplace.